A Stochastic Model for Adaptive Behavior in a Dynamic Situation - Jones, J. Morgan (Management Science, 1971)
A stochastic model of adaptive behavior in a dynamic situation is proposed, and its properties developed. The model is developed from a hypothetical construct of behavior, and, in the limit, becomes a nonstationary probability diffusion process. Although the model has wide potential applicability, it is discussed in the marketing context for which the model was first proposed. In addition to properties of the model, important aspects of the model as it applies to marketing will be discussed.